White-fly Epidemic in Holoptelea integrifolia Forest in Kanpur Zoological Park, Uttar Pradesh - Misra, R. M.; Mishra, R. K. (Indian Forester, 1995)
Epidemic infestation of Holoptelea integrifolia (Kanju) was reported for the first time in Allen Forest (Zoological Park) Kanpur in 1989. A study was undertaken in Septemher, 1989 to diagnose the epidemic and suggest control measures which is described in this paper.